The Effect of Using the Nesting Method and Prone Position on Changes in Oxygenation Status in Low Birth Weight Babies - Suriya, Melti; Prastiwi, Ikha; Marlina, Lina Marlina; Zuriati (Althar Cendikia Education, 2024)
Low birth weight babies is a public health problem because it is one of the causes of the high infant mortality rate (AKB). Prematurity is the 2nd cause of death in babies aged 0 - 6 days, which is caused by immaturity of almost all organs of the baby's body. Babies with BBLR are one of the risk factors that have various complications. Low birth weight babies who are quite large and susceptible to impaired vital functions that can affect the growth and development of the baby require proper treatment. The use of nesting is one of the recommended treatments for BBLR. This study aims to determine the effect of the use of nesting and prone position in premature infants on changes in oxygen saturation at Bhakti Husada Purwakarta Hospital in 2024. This study is a quantitative research using the quasi-experiment design method type one group pretest-posttest with a total of 15 respondents in the BBLR in the control group and 15 respondents in the intervention group. The conclusion of this study is that there is an effect of nesting and prone position on changes in oxygen saturation in BBLR. There was no significant effect of nesting on pulse frequency and BBLR breath rate. The use of nesting and prone positions can be used as a form of nursing intervention.